Composite multilayer memristor and preparation method thereof
By adopting a composite multilayer structure and an active electrode modulation layer with an arrayed through-hole in the memristor, the shortcomings of existing memristors in terms of stability, uniformity and durability are solved, and higher uniformity and Stability and simplify the preparation process and reduce costs.
Patent Information
- Application Number
- CN202510080307.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing memristors have shortcomings in terms of stability of resistance value conversion, uniformity of switching speed and durability of use, and the preparation process is complex and costly.
Memristors with composite multi-layer structures, including base layer, inert electrode layer, functional layer, active electrode modulation layer and active electrode layer, are deposited layer by layer through atomic layer growth technology and thermal evaporation technology to form arrayed through holes The active electrode modulation layer is used to realize array regulation of conductive filaments.
It significantly improves the uniformity and stability of the memristor, reduces operating voltage and power consumption, simplifies the preparation process, reduces costs, and makes it suitable for large-scale production.
Smart Images

Figure CN119522036A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microelectronic devices, and in particular relates to a composite multilayer memristor and a preparation method thereof. Background Art
[0002] With the rapid development of modern information technology, the performance of electronic devices plays a key and fundamental role in promoting progress in many fields. As an emerging electronic component, memristors have shown great application potential in many fields such as information storage, logic circuit design, and neuromorphic computing since their discovery. For example, traditional storage technologies such as disks and optical disks have gradually encountered bottlenecks in data storage density, read and write speeds, and power consumption. Memristors, with their unique adjustable resistance characteristics, can achieve high-density storage at the nanoscale while also having the advantages of low-power operation. They are expected to subvert existing technologies and become the core components of the next generation of storage technology. However, in practical applications, the performance of memristors still has many shortcomings, such as the stability of resistance conversion, the uniformity of switching speed, and the durability of use.
[0003] As the demand for high-performance, low-power, and highly integrated electronic systems becomes more urgent, how to overcome the existing performance defects of memristors and optimize them has become a research hotspot in the field of electronic technology. For example, Reference 1 (AThreshold Switching Selector Based on Highly Ordered Ag Nanodots for X-PointMemory Applications. Adv. Sci. 2019, 6, 1900024) and Reference 2 (High-UniformityThreshold Switching HfO2-Based Selectors with Patterned Ag Nanodots. Adv.Sci. 2020, 7, 2002251) achieved the preparation of highly uniform and highly stable memristors through arrayed active electrodes, but their harsh preparation conditions and high preparation costs limit their large-scale application.
[0004] For another example, a patent application with publication number US20220123208A1 discloses a memristor, including an active electrode, an inert electrode and a resistance switching layer, wherein the resistance switching layer includes a porous insulating layer and a conductive filament, wherein the porous insulating layer is disposed between the active electrode and the inert electrode, and the porous insulating layer has a through-channel hole; the conductive filament is formed in the through-channel hole. Using the porous insulating layer structure, this patent also preliminarily realizes the memristive characteristic. However, since the porous insulating layer is a through-hole structure, its dark current is large, so the switch is relatively small and the stability is poor. At the same time, the preparation of the through-hole structure requires an etching process, which is complicated and time-consuming. Summary of the invention
[0005] In order to solve the above technical problems existing in the prior art, the present invention provides a composite multilayer memristor and a preparation method thereof, which improves the uniformity and stability of the memristor while reducing the operating voltage, and the preparation process is simple.
[0006] The present invention provides a composite multilayer memristor, comprising a base layer and an inert electrode layer, a functional layer, an active electrode modulation layer and an active electrode layer sequentially formed on the base layer, wherein the functional layer and the active electrode modulation layer are both made of oxide materials, the active electrode modulation layer has arrayed through holes, and the active electrode layer has connection points extending along the through holes to the functional layer, and the connection points are used as arrayed active electrodes.
[0007] Preferably, the oxide materials used in the functional layer and the active electrode modulation layer are respectively one or more of aluminum oxide, hafnium oxide, silicon dioxide and zinc oxide. Aluminum oxide, hafnium oxide, silicon dioxide and zinc oxide have high dielectric constants and large resistance values, and can achieve memristive characteristics with high switching ratios. Further preferably, the oxide materials used in the functional layer and the active electrode modulation layer are both aluminum oxide.
[0008] Preferably, the thickness of the functional layer is 8~12 nm. Within this range, the memristor has a large switching ratio while the operating voltage is relatively small, resulting in a lower operating current and thus higher operating stability. The thickness of the functional layer is further preferably 10 nm; the thickness of the active electrode modulation layer is 3~8 nm. Within this range, the active electrode modulation layer can form stable arrayed through holes, thereby achieving arrayed regulation of the conductive filament formation sites. The thickness of the active electrode modulation layer is further preferably 5 nm.
[0009] Preferably, the substrate layer is a PET substrate, a silicon substrate or a quartz substrate, with a thickness of 100-300 μm; the inert electrode layer is Au or Pt, with a thickness of 20-40 nm; and the active electrode layer is Cu or Ag, with a thickness of 20-40 nm.
[0010] Preferably, an adhesion layer is provided between the substrate layer and the inert electrode layer; and an electrode protection layer is provided on the surface of the active electrode layer.
[0011] Preferably, the adhesion layer is Cr, Ni or Ti, with a thickness of 3-5 nm; the electrode protection layer is Au, with a thickness of 20-40 nm.
[0012] The present invention also provides a method for preparing the composite multilayer memristor, comprising the following steps: (2) depositing an adhesion layer on the surface of the substrate; (3) depositing an inert electrode layer on the surface of the adhesion layer; (4) growing a functional layer on the surface of the inert electrode layer; (5) growing an active electrode modulation layer on the surface of the functional layer; (6) depositing an active electrode layer on the surface of the active electrode modulation layer; (7) depositing an electrode protection layer on the surface of the active electrode layer; Wherein, in step (4), a precursor and an oxygen source reaction gas for forming a functional layer are circulated in sequence to achieve layer-by-layer growth of an oxide material of the functional layer; in step (5), a precursor and a reaction gas for forming an active electrode modulation layer are circulated in sequence to achieve layer-by-layer growth of an oxide material of the active electrode modulation layer; the molar ratio of the precursor and the oxygen source reaction gas for forming the active electrode modulation layer is not higher than the molar ratio of the precursor and the oxygen source reaction gas for forming the functional layer, and the temperature when growing the active electrode modulation layer is lower than the temperature when growing the functional layer, so that the active electrode modulation layer formed by growth has arrayed through holes, and the active electrode layer formed by deposition has connection points extending along the through holes to the functional layer.
[0013] Preferably, the molar ratio of the precursor to the oxygen source reaction gas used to form the functional layer is 1:1-4; the molar ratio of the precursor to the oxygen source reaction gas used to form the active electrode modulation layer is 1:1-6; the growth temperature when growing the functional layer in step (4) is 200-300°C; the growth temperature when growing the active electrode modulation layer in step (5) is 50-100°C. The relatively high growth temperature and the relatively precise raw material ratio make the functional layer have higher insulation to provide a larger switching ratio and lower dark current; the relatively low growth temperature and the molar ratio of the precursor to the oxygen source reaction gas make the active electrode modulation layer form a non-continuous arrayed through hole, and the diameter of the formed through hole and the connection point are preferably in the range of 50-500 nm.
[0014] Preferably, in step (4), for different functional layer materials, the process selection is as follows: ZnO: The raw materials are diethyl zinc (precursor) and water vapor (oxygen source), the raw material molar ratio is 1:1, and the growth temperature is 200~250 ℃; Al2O3: The raw materials are trimethylaluminum (precursor) and water vapor (oxygen source), the raw material molar ratio is 2:3, and the growth temperature is 250~300 ℃; HfO2: The raw materials are tetrakis(dimethylamino)hafnium (precursor, CAS: 19782-68-4) and ozone (oxygen source), the raw material molar ratio is 1:4, and the growth temperature is 200~300 ℃; SiO2: The raw materials are dichlorosilane (precursor) and water vapor (oxygen source), the molar ratio of the raw materials is 1:2, and the growth temperature is 200~250 ℃.
[0015] Preferably, in step (5), for different active electrode modulation layer materials, the process selection is as follows: ZnO: The raw materials are diethyl zinc (precursor) and water vapor (oxygen source), the molar ratio of raw materials is 1:1~2, and the growth temperature is 50~100 ℃; Al2O3: The raw materials are trimethylaluminum (precursor) and water vapor (oxygen source), the molar ratio of raw materials is 1:1.5~3, and the growth temperature is 50~75 ℃; HfO2: The raw materials are tetrakis(dimethylamino)hafnium (precursor) and ozone (oxygen source), the molar ratio of the raw materials is 1:4~6, and the growth temperature is 50~75 ℃; SiO2: The raw materials are dichlorosilane (precursor) and water vapor (oxygen source), the molar ratio of the raw materials is 1:2~3, and the growth temperature is 50~100 ℃.
[0016] Further preferably, in step (4), the raw materials are trimethylaluminum and water vapor, the raw material molar ratio is 2:3, and the growth temperature is 250°C; in step (5), the raw materials are trimethylaluminum and water vapor, the raw material molar ratio is 1:3, and the growth temperature is 50°C. The surface of the functional layer obtained in this way is more uniform and dense, the obtained active electrode modulation layer has more arrayed and more evenly distributed through holes, and the obtained memristor has better uniform stability.
[0017] Preferably, in step (2), the adhesion layer is deposited by high vacuum magnetron sputtering technology; in step (3), the inert electrode layer is deposited by high vacuum magnetron sputtering technology; in step (4), the functional layer is grown by atomic layer growth technology; in step (5), the active electrode modulation layer is grown by atomic layer growth technology; in step (6), the active electrode layer is deposited by thermal evaporation technology; in step (7), the electrode protection layer is deposited by thermal evaporation technology.
[0018] The working principle of the composite multilayer memristor of the present invention is as follows: a. The main function of the base layer is to provide support and provide a base for the entire device; b. The adhesion layer acts as a transition layer to improve the adhesion between the inert electrode and the substrate layer, thereby achieving stable adhesion of the inert electrode on the substrate layer; c. The inert electrode layer serves as a conductive end and has excellent conductive function, which can connect the memristor to the electric field. The inert electrode layer material is chemically stable, does not ionize under the electric field, does not react with the active electrode material, and exists as a cutoff material for the migration of the active electrode material along the electric field line; d. The active electrode layer material has a relatively active chemical property and can be ionized under the action of an electric field. The ions formed by ionization migrate to the inert electrode layer under the action of the electric field force. The migrating active electrode material can form a conductive path, i.e., a conductive filament, in the functional layer with insulating properties; e. The functional layer, as an insulating layer, is the core of providing resistive switching characteristics. Before active electrode materials pass through the functional layer to form conductive filaments, the functional layer provides a higher resistance. When conductive filaments are formed, the resistance of the functional layer decreases. After the electric field that drives the conductive filaments is removed, the functional layer can use its own lattice repulsion to cut off the conductive filaments, so that the device can restore a higher resistance, thereby realizing high-low resistance conversion; f. The active electrode modulation layer has an array of through holes, forming a connection point where the active electrode extends to the functional layer, thereby achieving array modulation of the active electrode; g. The active electrode protection layer is used to isolate the air and prevent the active electrode from being oxidized.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The composite multilayer memristor of the present invention is provided with an active electrode modulation layer with arrayed through holes, so that the atoms of the active electrode layer are pre-optimized by the active electrode array through the active electrode modulation layer before passing through the functional layer, and the arrayed regulation of the conductive filament formation site is realized, thereby significantly improving the uniformity and stability of the memristor. Different from the special active electrode array preparation process, the present invention can directly realize the continuous preparation of the functional layer and the active electrode modulation layer by regulating the preparation process of the functional layer, without the need for a complex preparation process, with low cost and large-scale preparation. At the same time, compared with the direct introduction of through holes, the present invention still retains a highly dense functional layer, with a lower dark current and less power consumption, and therefore has more application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a structural schematic diagram of the composite multilayer memristor of the present invention.
[0021] Figure 2 It is a scanning electron microscope image of the functional layer of the composite multilayer memristor in Example 1 of the present invention.
[0022] Figure 3This is a scanning electron microscope image of the active electrode modulation layer of the composite multilayer memristor in Example 1 of the present invention.
[0023] Figure 4 1 is a diagram showing the statistical distribution of the apertures of the active electrode modulation layer of the composite multilayer memristor in Example 1 of the present invention.
[0024] Figure 5 is a current-voltage response diagram of the composite multilayer memristor in Example 1 of the present invention after 100 cycles. The ordinate 1E-6 represents 1×10 -6 , the same below.
[0025] Figure 6 This is a graph showing the relationship between the threshold turn-on voltage and the number of cycles of the composite multilayer memristor under 100 cycles in Example 1 of the present invention.
[0026] Figure 7 This is a statistical distribution characteristic diagram of the threshold conversion voltage of the composite multilayer memristor under 100 cycles in Example 1 of the present invention.
[0027] Figure 8 This is a current-voltage response diagram of the memristor in comparative example 1 after 100 cycles.
[0028] Fig. 9 This is a current-voltage response relationship diagram of the composite multilayer memristor in Example 2 of the present invention after 100 cycles.
[0029] Fig.10 This is a current-voltage response diagram of the memristor in comparative example 2 after 100 cycles.
[0030] Fig.11 This is a current-voltage response diagram of the composite multilayer memristor in Example 3 of the present invention after 100 cycles.
[0031] Fig.12 This is a current-voltage response diagram of the memristor in comparative example 3 after 100 cycles.
[0032] Reference numerals: S110: base layer, S1101: adhesion layer, S1102: inert electrode layer, S1103: functional layer, S1104: active electrode modulation layer, S1105: active electrode layer, S1106: electrode protection layer. DETAILED DESCRIPTION
[0033] Example 1
[0034] A composite multilayer memristor and a method for preparing the same are as follows: 1) Ultrasonic cleaning of silicon substrate (100 μm) material was performed with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean silicon substrate surface.
[0035] 2) A 3 nm thick Cr adhesion layer was deposited on the surface of a clean silicon substrate by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Cr with a purity of 99.99%.
[0036] 3) A Pt inert electrode layer with a thickness of 40 nm was deposited on the surface of the Cr adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Pt with a purity of 99.99%.
[0037] 4) A 10 nm thick Al2O3 functional layer is grown on the surface of the inert electrode layer by an atomic layer deposition system. The specific process is as follows: The raw materials are trimethylaluminum and water, the raw material molar ratio is 2:3, and the growth temperature is 250°C. First, trimethylaluminum gas is introduced into the reaction chamber with a substrate temperature of 250°C to form a trimethylaluminum molecular film on the surface of the inert electrode. Then, water vapor is introduced into the chamber to react with the adsorbed trimethylaluminum molecular film layer to obtain a continuous and dense aluminum oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0038] like Figure 2 As shown, the surface of the prepared functional layer is uniform and dense. The functional layer serves as the core of resistance value transformation and provides a larger switching ratio for the memristor.
[0039] 5) A 5 nm thick Al2O3 active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are trimethylaluminum and water, the raw material molar ratio is 1:3, and the growth temperature is 50°C. First, trimethylaluminum gas is introduced into the reaction chamber with a substrate temperature of 50°C to form a trimethylaluminum molecular film on the surface of the functional layer. Then, water vapor is introduced into the chamber to react with the adsorbed trimethylaluminum molecular film layer to obtain a porous aluminum oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process is completed.
[0040] like Figure 3 As shown, arrayed through holes are formed in the prepared active electrode modulation layer, and the pore size statistics are as follows Figure 4 As shown, array modulation of active electrodes can be achieved, which promotes the formation of uniform conductive filaments and is a key link in the preparation of composite multilayer memristors.
[0041] 6) A 20 nm thick Ag active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4Pa, the steam material is Ag with a purity of 99.99%.
[0042] 7) A 40 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0043] Thus, the composite multilayer memristor is prepared. The structure of the composite multilayer memristor is as follows: Figure 1 shown.
[0044] Example 2
[0045] 1) Ultrasonic cleaning of silicon substrate (300 μm) was performed with acetone, isopropanol, ethanol and distilled water for 5 min in sequence to obtain a clean silicon substrate surface.
[0046] 2) A Ti adhesion layer with a thickness of 5 nm was deposited on the surface of a clean silicon substrate by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Ti with a purity of 99.99%.
[0047] 3) A Pt inert electrode layer with a thickness of 30 nm was deposited on the surface of the Ti adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Pt with a purity of 99.99%.
[0048] 4) Grow an Al2O3 functional layer with a thickness of 8 nm on the surface of the inert electrode layer using atomic layer growth technology. The specific process is as follows: The raw materials are trimethylaluminum and water, the raw material molar ratio is 2:3, and the growth temperature is 300 ° C. First, trimethylaluminum gas is introduced into the reaction chamber with a substrate temperature of 300 ° C to form a trimethylaluminum molecular film on the surface of the inert electrode. Then, water vapor is introduced into the chamber to react with the adsorbed trimethylaluminum molecular film layer to obtain a continuous and dense aluminum oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0049] 5) Grow an Al2O3 active electrode modulation layer with a thickness of 3 nm on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are trimethylaluminum and water, the raw material molar ratio is 1:1.5, and the growth temperature is 75°C. First, trimethylaluminum gas is introduced into a reaction chamber with a substrate temperature of 75°C to form a trimethylaluminum molecular film on the surface of the functional layer. Then, water vapor is introduced into the chamber to react with the adsorbed trimethylaluminum molecular film layer to obtain a porous aluminum oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process is completed.
[0050] 6) A 30 nm thick Cu active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Cu with a purity of 99.99%.
[0051] 7) A 20 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0052] Example 3
[0053] 1) Ultrasonic cleaning of PET substrate (150 μm) material was performed with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean PET substrate surface.
[0054] 2) A Ni adhesion layer with a thickness of 5 nm was deposited on the surface of a clean PET substrate by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Ni with a purity of 99.99%.
[0055] 3) An Au inert electrode layer with a thickness of 40 nm was deposited on the surface of the Ni adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Au with a purity of 99.99%.
[0056] 4) A HfO2 functional layer with a thickness of 8 nm is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are tetrakis(dimethylamino)hafnium and ozone, the raw material molar ratio is 1:4, and the growth temperature is 300°C. First, tetrakis(dimethylamino)hafnium gas is introduced into a reaction chamber with a substrate temperature of 300°C to form a layer of tetrakis(dimethylamino)hafnium molecular film on the surface of the inert electrode, and then ozone gas is introduced into the chamber to react with the adsorbed tetrakis(dimethylamino)hafnium molecular film layer to obtain a continuous and dense hafnium oxide material, and the preparation is repeated for multiple times until the target thickness is reached, and the preparation process ends.
[0057] 5) Grow an 8 nm thick HfO2 active electrode modulation layer on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are tetrakis(dimethylamino)hafnium and ozone, the raw material molar ratio is 1:4, and the growth temperature is 50°C. First, tetrakis(dimethylamino)hafnium gas is introduced into a reaction chamber with a substrate temperature of 50°C to form a tetrakis(dimethylamino)hafnium molecular film on the surface of the functional layer, and then ozone gas is introduced into the chamber to react with the adsorbed tetrakis(dimethylamino)hafnium molecular film layer to obtain a porous hafnium oxide material, and the preparation is repeated for multiple times until the target thickness is reached, and the preparation process ends.
[0058] 6) A 40 nm thick Cu active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Cu with a purity of 99.99%.
[0059] 7) A 30 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0060] Example 4
[0061] 1) Ultrasonic cleaning of silicon substrate (100 μm) material was performed with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean silicon substrate surface.
[0062] 2) A Ti adhesion layer with a thickness of 5 nm was deposited on the surface of a clean silicon substrate by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Ti with a purity of 99.99%.
[0063] 3) An Au inert electrode layer with a thickness of 20 nm was deposited on the surface of the Ti adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Au with a purity of 99.99%.
[0064] 4) A 10 nm thick HfO2 functional layer is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are tetrakis(dimethylamino)hafnium and ozone, the raw material molar ratio is 1:4, and the growth temperature is 200°C. First, tetrakis(dimethylamino)hafnium gas is introduced into a reaction chamber with a substrate temperature of 200°C to form a layer of tetrakis(dimethylamino)hafnium molecular film on the surface of the inert electrode, and then ozone gas is introduced into the chamber to react with the adsorbed tetrakis(dimethylamino)hafnium molecular film layer to obtain a continuous and dense hafnium oxide material, and the preparation is repeated for multiple times until the target thickness is reached, and the preparation process ends.
[0065] 5) A 3 nm thick HfO2 active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are tetrakis(dimethylamino)hafnium and ozone, the raw material molar ratio is 1:6, and the growth temperature is 75°C. First, tetrakis(dimethylamino)hafnium gas is introduced into a reaction chamber with a substrate temperature of 75°C to form a tetrakis(dimethylamino)hafnium molecular film on the surface of the functional layer, and then ozone gas is introduced into the chamber to react with the adsorbed tetrakis(dimethylamino)hafnium molecular film layer to obtain a porous hafnium oxide material, and the preparation is repeated for multiple times until the target thickness is reached, and the preparation process ends.
[0066] 6) A 25 nm thick Ag active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steam material is Ag with a purity of 99.99%.
[0067] 7) A 20 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0068] Example 5
[0069] 1) Ultrasonic clean the quartz substrate (100 μm) material with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean quartz substrate surface.
[0070] 2) A Ti adhesion layer with a thickness of 5 nm was deposited on the surface of a clean quartz substrate by magnetron sputtering technology. The magnetron chamber was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Ti with a purity of 99.99%.
[0071] 3) A Pt inert electrode layer with a thickness of 40 nm was deposited on the surface of the Ti adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Pt with a purity of 99.99%.
[0072] 4) A ZnO functional layer with a thickness of 12 nm is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are diethyl zinc and water, the raw material molar ratio is 1:1, and the growth temperature is 200 ° C. First, diethyl zinc gas is introduced into the reaction chamber with a substrate temperature of 200 ° C to form a layer of diethyl zinc molecular film on the surface of the inert electrode, and then water vapor is introduced into the reaction chamber to react with the adsorbed diethyl zinc molecular film layer to obtain a continuous and dense zinc oxide material, and the preparation is repeated for multiple times until the target thickness is reached, and the preparation process ends.
[0073] 5) A 3 nm thick ZnO active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are diethyl zinc and water, the raw material molar ratio is 1:2, and the growth temperature is 100 ° C. First, diethyl zinc gas is introduced into the reaction chamber with a substrate temperature of 100 ° C to form a diethyl zinc molecular film on the surface of the functional layer, and then water vapor is introduced into the reaction chamber to react with the adsorbed diethyl zinc molecular film layer to obtain a porous zinc oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0074] 6) A 20 nm thick Ag active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steam material is Ag with a purity of 99.99%.
[0075] 7) A 30 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0076] Example 6
[0077] 1) Ultrasonic cleaning of silicon substrate (150 μm) material was performed with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean silicon substrate surface.
[0078] 2) A Ti adhesion layer with a thickness of 5 nm was deposited on the surface of a clean silicon substrate by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Ti with a purity of 99.99%.
[0079] 3) A Pt inert electrode layer with a thickness of 30 nm was deposited on the surface of the Ti adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Pt with a purity of 99.99%.
[0080] 4) A ZnO functional layer with a thickness of 10 nm is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are diethyl zinc and water, the raw material molar ratio is 1:1, and the growth temperature is 250 ° C. First, diethyl zinc gas is introduced into the reaction chamber with a substrate temperature of 250 ° C to form a layer of diethyl zinc molecular film on the surface of the inert electrode, and then water vapor is introduced into the reaction chamber to react with the adsorbed diethyl zinc molecular film layer to obtain a continuous and dense zinc oxide material, and the preparation is repeated for multiple cycles until the target thickness is reached, and the preparation process ends.
[0081] 5) A 5 nm thick ZnO active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are diethyl zinc and water, the raw material molar ratio is 1:1, and the growth temperature is 50°C. First, diethyl zinc gas is introduced into a reaction chamber with a substrate temperature of 50°C to form a diethyl zinc molecular film on the surface of the functional layer, and then water vapor is introduced into the reaction chamber to react with the adsorbed diethyl zinc molecular film layer to obtain a porous zinc oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0082] 6) A 30 nm thick Cu active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Cu with a purity of 99.99%.
[0083] 7) A 20 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0084] Example 7
[0085] 1) Ultrasonic cleaning of silicon substrate (200 μm) was performed with acetone, isopropanol, ethanol and distilled water for 5 min in sequence to obtain a clean silicon substrate surface.
[0086] 2) A Ti adhesion layer with a thickness of 3 nm was deposited on the surface of a clean silicon substrate by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Ti with a purity of 99.99%.
[0087] 3) A Pt inert electrode layer with a thickness of 30 nm was deposited on the surface of the Ti adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Pt with a purity of 99.99%.
[0088] 4) A SiO2 functional layer with a thickness of 8 nm is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are dichlorosilane and water, the raw material molar ratio is 1:2, and the growth temperature is 250°C. First, dichlorosilane gas is introduced into the reaction chamber with a substrate temperature of 250°C to form a layer of dichlorosilane molecular film on the surface of the inert electrode. Then, water vapor is introduced into the chamber to react with the adsorbed dichlorosilane molecular film layer to obtain a continuous and dense silicon dioxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0089] 5) A 5 nm thick SiO2 active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are dichlorosilane and water, the raw material molar ratio is 1:3, and the growth temperature is 100°C. First, dichlorosilane gas is introduced into a reaction chamber with a substrate temperature of 100°C to form a dichlorosilane molecular film on the surface of the functional layer, and then water vapor is introduced into the chamber to react with the adsorbed dichlorosilane molecular film layer to obtain a porous silicon dioxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0090] 6) A 25 nm thick Cu active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Cu with a purity of 99.99%.
[0091] 7) A 25 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0092] Example 8
[0093] 1) Ultrasonic clean the quartz substrate (300 μm) material with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean quartz substrate surface.
[0094] 2) A 5 nm thick Cr adhesion layer was deposited on the surface of a clean quartz substrate by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Cr with a purity of 99.99%.
[0095] 3) An Au inert electrode layer with a thickness of 40 nm was deposited on the surface of the Cr adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Au with a purity of 99.99%.
[0096] 4) A SiO2 functional layer with a thickness of 10 nm is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are dichlorosilane and water, the molar ratio of the raw materials is 1:2, and the growth temperature is 200 ° C. First, dichlorosilane gas is introduced into the reaction chamber with a substrate temperature of 200 ° C to form a layer of dichlorosilane molecular film on the surface of the inert electrode. Then, water vapor is introduced into the chamber to react with the adsorbed dichlorosilane molecular film layer to obtain a continuous and dense silicon dioxide material. The preparation is repeated for multiple times until the target thickness is reached, and the preparation process ends.
[0097] 5) A 3 nm thick SiO2 active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are dichlorosilane and water, the molar ratio of the raw materials is 1:2, and the growth temperature is 50°C. First, dichlorosilane gas is introduced into the reaction chamber with a substrate temperature of 50°C to form a dichlorosilane molecular film on the surface of the functional layer. Then, water vapor is introduced into the chamber to react with the adsorbed dichlorosilane molecular film layer to obtain a porous silicon dioxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0098] 6) A 30 nm thick Ag active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steam material is Ag with a purity of 99.99%.
[0099] 7) A 30 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0100] Example 9
[0101] 1) Ultrasonic cleaning of PET substrate (150 μm) material was performed with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean PET substrate surface.
[0102] 2) A 3 nm thick Cr adhesion layer was deposited on the surface of a clean PET substrate by magnetron sputtering technology. The magnetron cavity contained a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Cr with a purity of 99.99%.
[0103] 3) An Au inert electrode layer with a thickness of 30 nm was deposited on the surface of the Cr adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Au with a purity of 99.99%.
[0104] 4) A HfO2 functional layer with a thickness of 8 nm is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are tetrakis(dimethylamino)hafnium and ozone, the raw material molar ratio is 1:2, and the growth temperature is 300°C. First, tetrakis(dimethylamino)hafnium gas is introduced into the reaction chamber with a substrate temperature of 300°C to form a layer of tetrakis(dimethylamino)hafnium molecular film on the surface of the inert electrode, and then ozone gas is introduced into the chamber to react with the adsorbed tetrakis(dimethylamino)hafnium molecular film layer to obtain a continuous and dense hafnium oxide material, and the preparation is repeated for multiple times until the target thickness is reached, and the preparation process ends.
[0105] 5) A 5 nm thick Al2O3 active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are trimethylaluminum and water, the raw material molar ratio is 1:3, and the growth temperature is 50°C. First, trimethylaluminum gas is introduced into the reaction chamber with a substrate temperature of 50°C to form a trimethylaluminum molecular film on the surface of the functional layer. Then, water vapor is introduced into the chamber to react with the adsorbed trimethylaluminum molecular film layer to obtain a porous aluminum oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0106] 6) A 20 nm thick Cu active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Cu with a purity of 99.99%.
[0107] 7) A 30 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1.5×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0108] Example 10
[0109] 1) Ultrasonic clean the silicon quartz substrate (250 μm) material with acetone, isopropanol, ethanol and distilled water for 5 minutes in sequence to obtain a clean quartz substrate surface.
[0110] 2) A Ti adhesion layer with a thickness of 5 nm was deposited on the surface of a clean quartz substrate by magnetron sputtering technology. The magnetron chamber was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Ti with a purity of 99.99%.
[0111] 3) A Pt inert electrode layer with a thickness of 35 nm was deposited on the surface of the Ti adhesion layer by magnetron sputtering technology. The magnetron cavity was filled with a mixture of nitrogen and argon with a gas volume ratio of 1:1 and a vacuum degree of 8 Torr. The target material was Pt with a purity of 99.99%.
[0112] 4) A SiO2 functional layer with a thickness of 10 nm is grown on the surface of the inert electrode layer using the atomic layer growth technique. The specific process is as follows: The raw materials are dichlorosilane and water, the raw material molar ratio is 1:2, and the growth temperature is 250°C. First, dichlorosilane gas is introduced into the reaction chamber with a substrate temperature of 250°C to form a layer of dichlorosilane molecular film on the surface of the inert electrode. Then, water vapor is introduced into the chamber to react with the adsorbed dichlorosilane molecular film layer to obtain a continuous and dense silicon dioxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0113] 5) A 5 nm thick Al2O3 active electrode modulation layer is grown on the surface of the functional layer using atomic layer growth technology. The specific process is as follows: The raw materials are trimethylaluminum and water, the raw material molar ratio is 1:3, and the growth temperature is 50°C. First, trimethylaluminum gas is introduced into the reaction chamber with a substrate temperature of 50°C to form a trimethylaluminum molecular film on the surface of the functional layer. Then, water vapor is introduced into the chamber to react with the adsorbed trimethylaluminum molecular film layer to obtain a porous aluminum oxide material. The preparation is repeated for multiple times until the target thickness is reached and the preparation process ends.
[0114] 6) A 20 nm thick Cu active electrode layer was deposited on the surface of the active electrode modulation layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Cu with a purity of 99.99%.
[0115] 7) A 40 nm thick Au electrode protective layer was deposited on the surface of the active electrode layer by thermal evaporation technology. The vacuum degree of the thermal evaporator chamber was 1×10 -4 Pa, the steaming material is Au with a purity of 99.99%.
[0116] Comparative Example 1
[0117] Different from Example 1, the manufactured memristor has no active electrode modulation layer.
[0118] Comparative Example 2
[0119] Different from Example 2, the manufactured memristor has no active electrode modulation layer.
[0120] Comparative Example 3
[0121] Different from Example 3, the manufactured memristor has no active electrode modulation layer.
[0122] Test Example 1
[0123] The active electrode layer and the inert electrode layer of the composite multilayer memristor prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were connected to the positive electrode and the negative electrode of the electrical testing equipment 2612 in sequence through tungsten probes to perform a memristor performance test. During the test, the current limit was 10 -7 A, the voltage step size was 0.03 V, and the applied voltage was scanned in a 0-1-0 V cycle.
[0124] For the test results of Example 1, Figure 5 The voltage-current curve relationship after 100 cycles is shown. In each cycle scan, the switching ratio of the memristor is large and the voltage is small, indicating that its memristor performance is excellent and the power consumption is low. The cycle stability results can be obtained by taking the memristor resistance conversion voltage as the ordinate and the scanning sequence as the abscissa, as shown in Figure 2. Figure 6 As shown in Figure 2, it can be seen that the turn-on voltage fluctuation of the memristor is small, so it is more stable. At the same time, the distribution of the memristor resistance conversion voltage is statistically analyzed, such as Figure 7 As shown in the figure, the turn-on voltage of the memristor is mainly concentrated in 0.08~0.11V, the turn-on voltage distribution is concentrated, and the performance is stable. In summary, the prepared memristor has a large switching ratio, low power consumption, excellent uniformity and stability, and great application potential. However, the memristor without an active electrode modulation layer in comparative example 1 has a large operating voltage and significant fluctuations, and its uniformity and stability are poor. Figure 8 shown.
[0125] For the test results of Example 2, Fig. 9 The voltage-current curve relationship after 100 cycles is shown. In each cycle scan, the switching ratio of the memristor is larger and the voltage is smaller, indicating that its memristor performance is excellent and the power consumption is low. At the same time, the turn-on voltage of the memristor is relatively concentrated, indicating that the uniformity and stability of the memristor resistance conversion voltage are good. However, the memristor without an active electrode modulation layer in Comparative Example 2 has poor uniformity and stability, such as Fig.10 shown.
[0126] For the test results of Example 3, Fig.11 The voltage-current curve relationship obtained after 100 cycles is shown. In each cycle scan, the switching ratio of the memristor is larger and the voltage is smaller, indicating that its memristor performance is excellent and the power consumption is low. At the same time, the turn-on voltage of the memristor is relatively concentrated, indicating that the uniformity and stability of the memristor resistance conversion voltage are good. However, the memristor without an active electrode modulation layer in Comparative Example 3 has poor uniformity and stability, such as Fig.12 shown.
Claims
1. A composite multilayer memristor, characterized in that: The invention comprises a base layer and an inert electrode layer, a functional layer, an active electrode modulation layer and an active electrode layer which are sequentially formed on the base layer. The functional layer and the active electrode modulation layer are both made of oxide materials. The active electrode modulation layer has arrayed through holes, and the active electrode layer has connection points extending along the through holes to the functional layer.
2. The composite multilayer memristor according to claim 1, characterized in that: The oxide materials used in the functional layer and the active electrode modulation layer are respectively one or more of aluminum oxide, hafnium oxide, silicon dioxide and zinc oxide.
3. The composite multilayer memristor according to claim 1, characterized in that: The thickness of the functional layer is 8-12 nm; The thickness of the active electrode modulation layer is 3-8 nm.
4. The composite multilayer memristor according to claim 1, characterized in that: The substrate layer is a PET substrate, a silicon substrate or a quartz substrate, and has a thickness of 100-300 μm; The inert electrode layer is Au or Pt, and has a thickness of 20-40 nm; The active electrode layer is Cu or Ag, and has a thickness of 20-40 nm.
5. The composite multilayer memristor according to claim 1, characterized in that: An adhesion layer is also provided between the substrate layer and the inert electrode layer; An electrode protection layer is also provided on the surface of the active electrode layer.
6. The composite multilayer memristor according to claim 5, characterized in that: The adhesion layer is Cr, Ni or Ti, and has a thickness of 3-5 nm; The electrode protection layer is Au with a thickness of 20-40 nm.
7. The method for preparing a composite multilayer memristor according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Cleaning the base material; (2) depositing an adhesion layer on the surface of the substrate; (3) depositing an inert electrode layer on the surface of the adhesion layer; (4) growing a functional layer on the surface of the inert electrode layer; (5) growing an active electrode modulation layer on the surface of the functional layer; (6) depositing an active electrode layer on the surface of the active electrode modulation layer; (7) depositing an electrode protection layer on the surface of the active electrode layer; Wherein, in step (4), a precursor and an oxygen source reaction gas for forming a functional layer are circulated in sequence to achieve layer-by-layer growth of an oxide material of the functional layer; in step (5), a precursor and an oxygen source reaction gas for forming an active electrode modulation layer are circulated in sequence to achieve layer-by-layer growth of an oxide material of the active electrode modulation layer; the molar ratio of the precursor and the oxygen source reaction gas for forming the active electrode modulation layer is not higher than the molar ratio of the precursor and the oxygen source reaction gas for forming the functional layer, and the temperature when growing the active electrode modulation layer is lower than the temperature when growing the functional layer, so that the active electrode modulation layer formed by growth has arrayed through holes, and the active electrode layer formed by deposition has connection points extending along the through holes to the functional layer.
8. The method for preparing a composite multilayer memristor according to claim 7, characterized in that: The molar ratio of the precursor and the oxygen source reaction gas used to form the functional layer is 1:1-4; The molar ratio of the precursor and the oxygen source reaction gas used to form the active electrode modulation layer is 1:1-6; The growth temperature of the functional layer in step (4) is 200-300°C; The growth temperature of the active electrode modulation layer in step (5) is 50~100°C.
9. The method for preparing a composite multilayer memristor according to claim 8, characterized in that: In step (4), for different functional layer materials, the process selection is as follows: ZnO: The raw materials are diethyl zinc and water vapor, the molar ratio of the raw materials is 1:1, and the growth temperature is 200~250 ℃; Al2O3: The raw materials are trimethylaluminum and water vapor, the molar ratio of the raw materials is 2:3, and the growth temperature is 250~300 ℃; HfO2: The raw materials are tetrakis(dimethylamino)hafnium and ozone, the molar ratio of the raw materials is 1:4, and the growth temperature is 200~300 ℃; SiO2: The raw materials are dichlorosilane and water vapor, the molar ratio of the raw materials is 1:2, and the growth temperature is 200~250 ℃; In step (5), for different active electrode modulation layer materials, the process selection is as follows: ZnO: The raw materials are diethyl zinc and water vapor, the molar ratio of the raw materials is 1:1~2, and the growth temperature is 50~100 ℃; Al2O3: The raw materials are trimethylaluminum and water vapor, the molar ratio of the raw materials is 1:1.5~3, and the growth temperature is 50~75 ℃; HfO2: The raw materials are tetrakis(dimethylamino)hafnium and ozone, the molar ratio of the raw materials is 1:4~6, and the growth temperature is 50~75 ℃; SiO2: The raw materials are dichlorosilane and water vapor, the molar ratio of the raw materials is 1:2~3, and the growth temperature is 50~100 ℃.
10. The method for preparing a composite multilayer memristor according to claim 7, characterized in that: In step (2), the adhesion layer is deposited by high vacuum magnetron sputtering technology; In step (3), an inert electrode layer is deposited by high vacuum magnetron sputtering technology; In step (4), the functional layer is grown using atomic layer growth technology; In step (5), an active electrode modulation layer is grown using an atomic layer growth technique; In step (6), the active electrode layer is deposited by thermal evaporation technology; In step (7), the electrode protection layer is deposited by thermal evaporation technology.
Citation Information
Patent Citations
Memristor having metal / ion channels formed in insulating layer and resistive switching memory device including the same
US20220123208A1
Resistance change type element and manufacturing method of the same
JP2016131216A
Memory cell and method of forming the same
US20210013407A1
Low current RRAM-based crossbar array circuits implemented with interface engineering technologies
US20220006008A1